(untitled) (Vallis Aurea, 2018)
By content and contribution, this paper focuses on trying to find out what elements are needed and how to engage in defining and creating a corporate vision. For operationalization, five groups of elements have been selected: basic corporate values, corporate identity and its recognition in the environment, competitive ability and acquired competitive advantage, great and exciting corporate goals, corporate values for all stakeholders. It has operated with 25 variables. The research sought to achieve two goals: to identify which elements are key to creating a corporate vision and whether they point to the creation of corporate values for all stakeholders? Evaluation and valorisation of these variables was done using a five-stage Likert scale. The claims were evaluated on a quota, representative sample of 100 managers in hotel systems in Dalmatia in 2016. A model of exploratory factor analysis was applied. Factor rotation was orthogonal with qurtimax. The factoring results showed that with 14 extracted factors approaching up to 92% of the common variance of all 25 included variables. With only six extracted factors, 63% of common variance is explained, with eight included extracted factors of 76% of common variance. Their visions of the investigated corporation are mostly based on experiential and "hard" variables. It was also found that the elements that point to the creation of corporate values for all corporate stakeholders were not primarily relevant to the creation of visions in relation to other elements.